2017
DOI: 10.1111/ijfs.13508
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic and antioxidant capacities of polysaccharides obtained from Laminaria japonica by different extraction media in diet‐induced mouse model

Abstract: Summary This study shows the industrial feasibility of using aqueous methods to produce antioxidative and hypolipidaemic polysaccharides from Laminaria japonica (LJP). Comparison was firstly made among the polysaccharides prepared using different extraction media, that is water alone (LJPW) and citric acid (LJPC), sulphuric acid, hydrochloric acid and phosphoric acid. LJPC enabled the highest extract yield (~11% dry weight), bile salt adsorption rate (~59% dry weight), ABTS radical scavenging activity (IC50 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The neuroprotective effects of the phenolic extracts could be linked to the radical scavenging and metal chelating activities of some of the bioactive constituents, which include phloroglucinol, ferulic acid, dihydroxybenzoic acid, 3,7-dimethyl quercetin, 5,7-dimethoxyflavone, dihydronaringenin-O-sulfate, apigenin, 7,2,4-trihydroxyisoflavanol, and kaempferol 3-(6-acetyl galactoside)7-rhamnose [41,84,85]. Polysaccharides such as fucoidans, alginates isolated from Sargassum spp., Laminaria japonica , Cystoseira trinodi, and Nizimuddinia zanardini [86,87,88,89,90,91], as well as protein extracts obtained from Ulva spp. and Gracilaria spp.…”
Section: Therapeutic Role Of Some Macroalgae In the Management Of Admentioning
confidence: 99%
“…The neuroprotective effects of the phenolic extracts could be linked to the radical scavenging and metal chelating activities of some of the bioactive constituents, which include phloroglucinol, ferulic acid, dihydroxybenzoic acid, 3,7-dimethyl quercetin, 5,7-dimethoxyflavone, dihydronaringenin-O-sulfate, apigenin, 7,2,4-trihydroxyisoflavanol, and kaempferol 3-(6-acetyl galactoside)7-rhamnose [41,84,85]. Polysaccharides such as fucoidans, alginates isolated from Sargassum spp., Laminaria japonica , Cystoseira trinodi, and Nizimuddinia zanardini [86,87,88,89,90,91], as well as protein extracts obtained from Ulva spp. and Gracilaria spp.…”
Section: Therapeutic Role Of Some Macroalgae In the Management Of Admentioning
confidence: 99%
“…Polysaccharides, natural polymers involved in numerous processes, are the major active components in Dendrobium orchids (Fan et al, 2009;Wang et al, 2010). There are many advantageous properties of polysaccharides, including nontoxicity, lack of side effects, improvement of immunity and antitumour, antidiabetic, hypolipidemic and antioxidant properties Yao et al, 2017). As polysaccharides are safe as functional food sources and have become more popular in recent years, it is important to conduct a value-oriented inquiry about D. aphyllum polysaccharides (Gao et al, 2017;Wee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al (2016) reported that a polysaccharide [mole ratio of galactose, mannose and fucose (26.1:1.3:1) and 1,3-and 1-linked galactose] separated from L. japonica had remarkably high oxygen radical absorbance capacity (1247.22 μmol trolox equants g −1 ) and ABTS (−70% at 4mg/mL) scavenging activities (Cui et al, 2016). In another similar study, antioxidant effect of polysaccharide separated from L. japonica was documented by Yao et al (2017). In this study, the authors compared the antioxidant capacity of polysaccharide extracted from different extraction methods such as water extraction and acidic extraction (citric acid, sulfuric acid, hydrochloric acid, and phosphoric acid).…”
Section: Antioxidant Abilitymentioning
confidence: 80%
“…In this study, the authors compared the antioxidant capacity of polysaccharide extracted from different extraction methods such as water extraction and acidic extraction (citric acid, sulfuric acid, hydrochloric acid, and phosphoric acid). According to the results, polysaccharides from citric acid aided extraction method had good ABTS radical scavenging activity (IC 50 = 1.06 mg/mL) and oxygen radical absorbance capacity (341.87 μmol trolox equants g −1 ) under the test conditions (Yao et al, 2017). In addition, antioxidant properties of pigment-free fucoidan separated from L. japonica was also reported (Zhao et al, 2018).…”
Section: Antioxidant Abilitymentioning
confidence: 89%